1997
DOI: 10.1016/s0006-3495(97)78240-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cation binding in ZnCl2-regenerated bacteriorhodopsin by x-ray absorption fine structures: effects of removing water molecules and adding Cl- ions

Abstract: The binding of Zn2+ in Zn2+-regenerated bacteriorhodopsin (bR) was studied under various conditions by x-ray absorption fine structures (XAFS). The 0.9:1 and 2:1 Zn2+:bR samples gave similar XAFS spectra, suggesting that Zn2+ might have only one strong binding site in bR. It was found that in aqueous bR solution, Zn2+ has an average of six oxygen or nitrogen ligands. Upon drying, two ligands are lost, suggesting the existence of two weakly bound water ligands near the cation-binding site in bacteriorhodopsin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The structural model of the cation-binding site includes only oxygens of carbonyl groups in the backbone and water molecules as the ligands of the bound cation. This kind of cation-binding site is consistent with the structures of the cation-binding sites proposed by x-ray absorption studies, which are suggested to include oxygen atoms as ligands (Zhang et al, 1997;Engelhard et al, 1987;Sepulcre et al, 1996).…”
Section: Specific Sites For Cation Bindingsupporting
confidence: 88%
“…The structural model of the cation-binding site includes only oxygens of carbonyl groups in the backbone and water molecules as the ligands of the bound cation. This kind of cation-binding site is consistent with the structures of the cation-binding sites proposed by x-ray absorption studies, which are suggested to include oxygen atoms as ligands (Zhang et al, 1997;Engelhard et al, 1987;Sepulcre et al, 1996).…”
Section: Specific Sites For Cation Bindingsupporting
confidence: 88%
“…Thus, Tuzi et al using 13 C NMR techniques proposed the existence of a cation binding site located on the loop between helices F and G,14 Eliash et al have shown a Mn 2+ ‐specific binding site on the extracellular part of the membrane,15 and Sanz et al established Glu194 and Glu204 as residues involved in cation binding 16. In addition, a high‐affinity binding site located near the retinal pocket had also been suggested by several authors 17–24…”
Section: Introductionmentioning
confidence: 93%